Methane Hydrate Formation and Dissocation in a Partially Saturated Sand--Measurements and Observations - Kneafsey, Timothy J.; Tomutsa, Liviu; Moridis, George J.; Seol, Yongkoo; Freifeld, Barry; Taylor, Charles E.; Gupta, Arvind (Lawrence Berkeley National Laboratory, 2005)
We performed a sequence of tests on a partially water-saturated sand sample contained in an x-ray transparent aluminum pressure vessel that is conducive to x-ray computed tomography (CT) observation. These tests were performed to gather data for estimation of thermal properties of the sand/water/gas system and the sand/hydrate/water/gas systems, as well as data to evaluate the kinetic nature of hydrate dissociation. The tests included mild thermal perturbations for the estimation of the thermal properties of the sand/water/gas system, hydrate formation, thermal perturbations with hydrate in the stability zone, hydrate dissociation through thermal stimulation, additional hydrate formation, and hydrate dissociation through depressurization with thermal stimulation. Density changes throughout the sample were observed as a result of hydrate formation and dissociation, and these processes induced capillary pressure changes that altered local water saturation.